The Use of Local Malay and Woirata in Social Media - Nazarudin (Nusa, 2021)
In this study, I investigated the language used by the Woirata community on Kisar Island in the Facebook groups “Putra Putri Oirata” and “Keluarga Manheri Mauhara”. I classified the language used in the posts and comments on each Facebook group to capture the language repertoires of the Woirata people on social media. The data show that the Woirata community uses a different variety in different domains: formal Indonesian for obituaries and politics, local Malay (MTJ, or Far East Malay) for daily conversations and comments on politics, and Woirata for self-expressive comments. Younger users employ innovative orthography understood only among the younger MTJ users, boasting about their creativity. From the data, it can be seen that they have developed a new lingua franca on the Internet that can be defined as a new “writing orality”.